Application of Urban Geology in Construction Projects (Case Study: Urban Geology of Sarpol-e Zahab, Kermanshah Province, Iran) - Sajad Afzali; Faezeh Taheri Sarmad; Mojtaba Heidari; Seyed Hossein Jalali (Indonesian Journal of Geography, 2021)
Urban geology is a preliminary study for the construction and development of cities, which has been more prominent in recent decades in some countries despite its long application history. It assesses the impact of geological and natural phenomena on urban space and available structures. The earthquake on Nov. 21, 2017, inflicted a lot of damage to the city of Sarpol-e Zahab, west of Iran, including financial losses and casualties. Reconstruction of this city and planning for its sustainable development entail conducting urban geological studies. In the present study, the effect of natural phenomena on Sarpol-e Zahab County was studied by investigating its geology and geomorphology. The results showed that, in addition to the earthquake that habitually affected the city of Sarpol-e Zahab, the hazards of other phenomena are also significant. Recorded horizontal acceleration in the recent earthquake confirmed the high seismicity of Sarpol-e Zahab has.